Epigenetic Library Screen Identifies Abexinostat as Novel Regulator of Adipocytic and Osteoblastic Differentiation of Human Skeletal (Mesenchymal) Stem Cells. (18th May 2016) - Ali, Dalia; Hamam, Rimi; Alfayez, Musaed; Kassem, Moustapha; Aldahmash, Abdullah; Alajez, Nehad M.
Abstract: : The epigenetic mechanisms promoting lineage-specific commitment of human skeletal (mesenchymal or stromal) stem cells (hMSCs) into adipocytes or osteoblasts are still not fully understood. Herein, we performed an epigenetic library functional screen and identified several novel compounds, including abexinostat, which promoted adipocytic and osteoblastic differentiation of hMSCs. Using gene expression microarrays, chromatin immunoprecipitation for H3K9Ac combined with high-throughput DNA sequencing (ChIP-seq), and bioinformatics, we identified several key genes involved in regulating stem cell proliferation and differentiation that were targeted by abexinostat. Concordantly, ChIP-quantitative polymerase chain reaction revealed marked increase in H3K9Ac epigenetic mark on the promoter region of AdipoQ, FABP4, PPARγ, KLF15, CEBPA, SP7, and ALPL in abexinostat-treated hMSCs. Pharmacological inhibition of focal adhesion kinase (PF-573228) or insulin-like growth factor-1R/insulin receptor (NVP-AEW51) signaling exhibited significant inhibition of abexinostat-mediated adipocytic differentiation, whereas inhibition of WNT (XAV939) or transforming growth factor-β (SB505124) signaling abrogated abexinostat-mediated osteogenic differentiation of hMSCs. Our findings provide insight into the understanding of the relationship between the epigenetic effect of histone deacetylase inhibitors, transcription factors, and differentiation pathways governing adipocyte and osteoblast differentiation. Manipulating such pathways allows a novel use for epigenetic compounds in hMSC-based therapies and tissue engineering. Significance: This unbiased epigenetic library functional screen identified several novel compounds, including abexinostat, that promoted adipocytic and osteoblastic differentiation of human skeletal (mesenchymal or stromal) stem cells (hMSCs). These data provide new insight into the understanding of the relationship between the epigenetic effect of histone deacetylase inhibitors, transcription factors, and differentiation pathways controlling adipocyte and osteoblast differentiation of hMSCs. Manipulating such pathways allows a novel use for epigenetic compounds in hMSC-based therapies for tissue engineering, bone disease, obesity, and metabolic-disorders. Abstract : Bexinostat is a novel compound promoting adipocytic and osteoblastic differentiation of human skeletal (mesenchymal or stromal) stem cells (hMSCs). It provides new insight into the understanding of the relationship between epigenetic effect of histone deacetylase inhibitors, transcription factors, and differentiation pathways governing adipocyte and osteoblast differentiation. Manipulating such pathways provides a novel use for epigenetic compounds in hMSC-based therapies.